Room Temperature Ferromagnetism in Gadolinium-doped Gallium Nitride. (9th January 2018) - Saravade, Vishal G.; Ferguson, Cameron H.; Ghods, Amirhossein; Zhou, Chuanle; Ferguson, Ian T.
ABSTRACT: Anomalous Hall effect was observed at room temperature in MOCVD-grown GaGdN from a (TMHD)3 Gd source, which can contain oxygen in its organic ligand. GaN, and GaGdN grown using a Cp3 Gd precursor which does not contain oxygen only showed the ordinary Hall effect. This indicates that oxygen could have a role in magnetic properties of GaGdN. The relationship between the anomalous Hall conductivity and longitudinal conductivity indicated that metallic conduction, hopping of carriers, and scattering-independent mechanisms are likely responsible for the ferromagnetism. However, this still requires further clarification.